Damascene Mamluk Extramuros Religious Heritage (14th and 15th Centuries): The Case of the as-Sanğaqdāre Mosque - Fayyad, Imane (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2019)
The as-Sanğaqdāre mosque, object of this paper, is located outside of the wall of Damascus. It carries the cadastral numbers 83 and 1121 in the Baḥṣah-as-Sanğaqdār region. It contains a large number of Mamluk vestiges from the 14th century. It is its north-eastern exterior facades, its minaret and its mausoleum leading to the sanctuary of the mosque through a door that grant it an architectural interest. This study makes the case that this mosque dates back from the Mamluk period. To that end, I will analyse relevant architectural and decorative features.